Leptospiral infection, pathogenesis and Its diagnosis-a review - Samrot, Antony V; Sean, Tan Chuan; Bhavya, Karanam Sai; Sahithya, Chamarthy Sai; Chandrasekaran, SaiPriya; Palanisamy, Raji; Robinson, Emilin Renitta; Subbiah, Suresh Kumar; Mok, Pooi Ling (Multidisciplinary Digital Publishing Institute, 2021)
Leptospirosis is a perplexing conundrum for many. In the existing literature, the pathophysiological mechanisms pertaining to leptospirosis is still not understood in full. Considered as a neglected tropical zoonotic disease, leptospirosis is culminating as a serious problem worldwide, seemingly existing as co-infections with various other unrelated diseases, including dengue and malaria. Misdiagnosis is also common as non-specific symptoms are documented extensively in the literature. This can easily lead to death, as the severe form of leptospirosis (Weil’s disease) manifests as a complex of systemic complications, especially renal failure. The virulence of Leptospira sp. is usually attributed to the outer membrane proteins, including LipL32. With an armament of virulence factors at their disposal, their ability to easily adhere, invade and replicate within cells calls for a swift refinement in research progress to establish their exact pathophysiological framework. As an effort to reconstitute the current knowledge on leptospirosis, the basis of leptospiral infection, including its risk factors, classification, morphology, transmission, pathogenesis, co-infections and clinical manifestations are highlighted in this review. The various diagnostic techniques are also outlined with emphasis on their respective pros and cons.